Correlation between cardiac magnetic resonance feature tracking derived left ventricular strain and morphological characteristics of non-ischemic dilated cardiomyopathy at baseline and follow-up. (14th October 2021) - Pozo Osinalde, E; Urmeneta Ulloa, J; Rodriguez Hernandez, J L; Perez De Isla, L; Martinez Fernandez, H; Islas, F; Marcos-Alberca, P; Mahia, P; Cobos, M A; Hernandez, P; Luaces, M; Gomez De Diego, J J; et al.
Abstract: Background: Left ventricular (LV) strain from echocardiography is a known useful predictor of LVEF recovery in non-ischemic dilated cardiomyopathy (NIDCM). More recently, feature tracking (FT) has allowed LV myocardial deformation analysis using conventional cardiac magnetic resonance (CMR) cine sequences. Purpose: Our aim is to establish the correlation between LV strain values from CMR-FT at diagnosis and morphological parameters at baseline and during follow-up. Methods: Consecutive patients with NIDCM who underwent CMR were retrospectively collected. All the studies were performed in a 1.5 Tesla magnet following a standard acquisition protocol of conventional SSFP cine sequences in long and short axis. Global longitudinal, circumferential and radial strain (GLS, GCS and GRS, respectively) were obtained with a dedicated FT software. Correlation with CMR morphological parameters at baseline were evaluated. Likewise, in the cases with follow-up echocardiogram association between FT LV strain and evolution of morphofunctional variables was explored. Results: CMR-FT strain analysis was performed in 98 patients (age 68±13 years, 72% males) with NIDCM. They showed severe LV dilatation (LVEDVi= 133.6±33.4 mL/m 2 ) and systolic dysfunction (LVEF= 29.5±9.6%) at baseline. Myocardial fibrosis was detected in 38.8% of the patients with late gadolium enhancement (LGE) sequence. All the basal CMR morphological characteristics were significantly correlated with FT strain analysis (Table), even more markedly for GCS. However, there was no association of baseline morphofunctional parameters with LGE. An echocardiogram was performed in 85.7% of the patients during the follow-up (2.4 [1.8–3.4] years), with an LVEF >50% in the 25.5% of the cases. These patients with preserved LVEF in the evolution showed better GCS (−9 vs −7.1%; p=0.019) at baseline, with no differences in the other FT LV strain parameters. Despite less fibrosis in LGE (16.1% vs 37.7%; p=0.037), none of the baseline morphofunctional CMR parameters (LVEF, LVEDVi...) were associated with systolic function restoration. In multivariate analysis, GCS was the only independent predictor (OR 1.16; p=0.045) of LVEF recovery among imaging variables. Conclusions: All the FT derived LV strain values were correlated with the degree of basal morphofunctional involvement in NIDCM. Furthermore, GCS emerged as an independent imaging predictor of LV systolic function restoration in our series. Funding Acknowledgement: Type of funding sources: None.